Living with climate change : Community Vulnerability and Adaptation in Ulukhaktok - Pearce, T; Goose, A; Inuktalik, R; Kataoyak, F; Okheena, G; Smit, B; Wandel, J; Beasley, E; Duerden, F (ArcticNet Inc., 2005)
No abstract available